Microfacies analysis of the Palaeocene Lockhart limestone on the eastern margin of the Upper Indus Basin (Pakistan): Implications for the depositional environment and reservoir characteristics. (15th February 2023) - Bilal, Ahmer; Yang, Renchao; Janjuhah, Hammad Tariq; Mughal, Muhammad Saleem; Li, Yang; Kontakiotis, George; Lenhardt, Nils
Abstract: A detailed sedimentological analysis of the Palaeocene Lockhart Limestone has been conducted to evaluate the depositional environment, diagenetic processes and hydrocarbon potential of the eastern margin of the Upper Indus Basin. From bottom to top, there are three microfacies recorded. The lower microfacies, composed of fine‐grained micrite and some diagenetic dolomite, reflect the low energy and calm palaeo‐current in the shallower section (1–2 m) of the inner shelf close to shore. The middle microfacies contain algae that suggest 5–15 m of water depth, especially along the inner‐middle shelf, but fractured and mixed bioclasts in micrite material indicate calm to moderately active water close to the wave base. Progressing from the lower microfacies to the middle microfacies, a gradual shift from orthochem to allochem components is observed. The top microfacies is dominated by massive benthic microfossils, indicating moderate energy‐water conditions with normal salinity. However, the presence of limestone intraclasts surrounded by microspar, miliolids and nummulites at the top indicates a high‐energy environment with increasing salinity and water depths from 20 to 130 m. These findings show that the Lockhart Limestone was deposited in a shallow shelf environment, spanning the inner‐mid shelf. Diagenetic processes observed include micritisation, cementation, dissolution, replacement, physical and chemical compaction, and fracture filling by calcite cement. The Lockhart Limestone represents a deepening upward sequence deposited below the shelf margin system tract and highstand systems tract in a regressive environment that could reflect good reservoir characteristics, has the potential to serve as an excellent hydrocarbon reservoir rock, and could be a primary target for future hydrocarbon exploration. Abstract : The Lockhart Limestone represents a deepening upward sequence deposited underneath the shelf margin system tract and highstand systems tract in a regressive environment that could reflect good reservoir characteristics, has the potential to serve as an excellent hydrocarbon reservoir rock, and could be a primary target for future hydrocarbon exploration.